Supporting paediatric patients: Parental presence in the anaesthetic journey - Blake, Salina (Operating Room Nurses Association of Canada Journal, 2020)
Objective This discussion paper explores the use of parental presence during induction of anaesthesia as a method of decreasing paediatric and parental perioperative anxiety. Setting A perioperative department in an Australian public hospital. Subjects Paediatric patients and parents/ guardians. Primary argument There is evidence to support the importance of parental presence in the anaesthetic setting; however, this varies between different health care facilities. This paper will argue that the presence of the parent during induction of anaesthesia will decrease the anxiety of the child. However, there has been little discussion about the pivotal role parents can play when participating in the anaesthetic process. Parents need to be given a clear orientation and specific instruction regarding their role during induction of anaesthesia to ensure that the child’s anaesthesia is safe. Conclusion Parental presence during induction of anaesthetic of a child may be a controversial practice in some hospitals; however, evidence states that it can reduce anxiety for the child. The presence of the parent working alongside the anaesthetic team combined with insight and understanding provided by a preoperative visit can assist in reducing anxiety for the child and parent.